Iron man (2020), volume 3 ebook Books of korvac iii - cosmic iron man. - Cantwell, Christopher (Iron Man (2020),, 2022)
Collects Iron Man (2020) #12-19. Iron Man is marooned in a small colony on a remote planet! A message from home warns him that Korvac is still a threat, but recovering from his injuries means pain medication - which might mean a relapse. Will Tony succumb to the temptation that has plagued him for years? Either way, Iron Man will soon face a cosmic showdown on the deck of Galactus' worldship. And to survive, he must battle Korvac's zealous and powerful disciples: Controller, Unicorn, Blizzard and a robotically enslaved Original Human Torch! Tony could use some friends, but does Doctor Doom count?! When the dust settles, Iron Man will emerge majorly upgraded and forever changed! But with great power comes great ego, and now his friends on Earth must decide: Has Tony Stark become an Iron God, or a dangerous threat?